The effect of Visual Display Unit (VDU) near task under two different surrounding lightings on accommodation facility / Azmir Ahmad, Ai-Hong Chen and Abd Rahim Ahmad - Ahmad, Azmir; Chen, Ai-Hong; Ahmad, Abd Rahim (Penerbit UiTM (UiTM Press), 2015)
The purpose of the study was to compare the accommodation facility after electronic visual display usage was used under two different surrounding lightings: one with and the other without room light. Accommodation facility is the capability of the eyes to respond and focus on visual stimuli at various distances, and could be measured clinically. Twenty young subjects participated in this study where the subjects were assigned to read binocularly from electronic visual display unit (VDU) for one hour under 2 different surrounding lighting conditions (with and without room light) at random sequence. Binocular accommodation facility was measured via standard clinical vision examination protocol using a ±2.00 DS lens flipper with 6/9 near visual acuity target. Friedman test showed no significant changes in binocular accommodation facility, [x2 (2) =5.772,p=0.06J. The difference in accommodation facility after one-hour VDU near task between the absence and presence of surrounding room light was negligible. Future studies should investigate the temporal aspects of the accommodation process during VDU task to understand the accommodation related VDU symptoms especially under low lighting.